A Circularly Polarized HTS Microstrip Antenna Array with Controllable Cryostat - Xiaoyong Zeng; Kama Huang; Zhongxia Hu; Qian Chen; Wei Xiao (International Journal of Antennas and Propagation, 2017)
A high-temperature superconductor (HTS) microstrip antenna array with right-hand circular polarization is proposed for space communications. The proposed HTS antenna array can achieve high efficiency, which is able to reduce the antenna’s loss. The array consists of 16 antenna elements being fed by a T-network. A pair of symmetric meander slots is used in each antenna element to broaden the input matching bandwidth. A controllable cryostat is used as the refrigeration for HTS. The experiment shows that the gain of the proposed HTS antenna is 8.39 dB, whose 10 dB return loss bandwidth is 2.2% ranging from 5.75 GHz to 5.87 GHz. In comparison with a traditional conductor antenna array having the same configuration, the proposed array has an 8.1 dB improvement in the gain and a 69.2% enhancement in the radiation efficiency.